2019
DOI: 10.1167/iovs.18-26049
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone Application to the Rat Forehead Produces Corneal Antinociception

Abstract: PurposeOcular pain and discomfort are the most defining symptoms of dry eye disease. We determined the ability of topical progesterone to affect corneal sensitivity and brainstem processing of nociceptive inputs.MethodsProgesterone or vehicle gel was applied to the shaved forehead in male Sprague Dawley rats. As a site control, gel also was applied to the cheek on the side contralateral to corneal stimulation. Corneal mechanical thresholds were determined using the Cochet-Bonnet esthesiometer in intact and lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 57 publications
(85 reference statements)
0
3
0
Order By: Relevance
“…1% progesterone gel administered on the forehead was found to reduce the frequency and severity of symptoms in individuals with coGVHD after 6 weeks compared to placebo (SANDE; scale: 0–100) (progesterone: mean reduction: −26.3, standard error [SE]: 4.1 vs. placebo: −5.6, SE: 5.8) as well as signs after 2 weeks compared to placebo (CFS) (progesterone: mean reduction: −2.5, SE: 0.5 vs. placebo: −0.2, SE: 0.8, p < 0.05) 128 . In rats with intact or excised lacrimal glands, 1% progesterone was found to provide corneal antinociception 129 . More data are needed on the impact of hormones as a treatment for GVHD.…”
Section: Treatment Of Gvhd Ogvhd and Dedmentioning
confidence: 93%
See 1 more Smart Citation
“…1% progesterone gel administered on the forehead was found to reduce the frequency and severity of symptoms in individuals with coGVHD after 6 weeks compared to placebo (SANDE; scale: 0–100) (progesterone: mean reduction: −26.3, standard error [SE]: 4.1 vs. placebo: −5.6, SE: 5.8) as well as signs after 2 weeks compared to placebo (CFS) (progesterone: mean reduction: −2.5, SE: 0.5 vs. placebo: −0.2, SE: 0.8, p < 0.05) 128 . In rats with intact or excised lacrimal glands, 1% progesterone was found to provide corneal antinociception 129 . More data are needed on the impact of hormones as a treatment for GVHD.…”
Section: Treatment Of Gvhd Ogvhd and Dedmentioning
confidence: 93%
“…128 In rats with intact or excised lacrimal glands, 1% progesterone was found to provide corneal antinociception. 129 More data are needed on the impact of hormones as a treatment for GVHD.…”
Section: Targeting Ocular Surface Inflammationmentioning
confidence: 99%
“…Although estrogen has been reported to be both pronociceptive and antinociceptive in various pain models, 22,[25][26][27][28][29] the research literature exclusively reports that progesterone is anti-inflammatory and antinociceptive . [30][31][32][33][34][35][36] We have recently reported that estrogen increases pain behaviors in a rat model of inflammatory TMD pain which is reversed with progesterone treatment. 37 Progesterone is also metabolized by 5α-reductase to 5α-dihydroprogesterone, which is then converted to the metabolite allopregnanolone by 3α-hydroxysteroid dehydrogenase (3α-HSD), thus progesterone's protective effects can occur through its metabolite allopregnanolone.…”
Section: Introductionmentioning
confidence: 99%